PENGGUNAAN METODE PAKEM UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MENULIS PANTUN SISWA KELAS IX-A SMP NEGERI 5 TENGGARONG - NFN Jumairi (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2016)
The aim of this research is to improve students’ activity and learning outcomes in writing a traditional poetry using pakem method. It is a classroom action research held in SMPN 5 Tenggarong,  Kutai Kartanegara Regency, in the odd semester in academic year 2015/2016. The research object is the students of IX-A. It uses some steps, such as planning, actuating, observing/evaluating, and reflecting. It can be concluded that there are students’ activity and learning outcome improvement in the academic year 2015/2016 in writing a traditional poetry using PAKEM method.